Manajemen Sumber Daya Manusia dalam Meningkatkan Mutu Pendidikan di RA – Alfatah - Iis Nurkamilah; Makmur Makmur (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze human resource management in improving the quality of education at RA Al-Fatah, focusing on four aspects: planning, recruitment, training and development, as well as monitoring and evaluation. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation. The findings show that: (1) HR planning involves strategy formulation such as RPP, RPPH, and task division among vice principals; (2) recruitment is conducted through two models—government-based and committee-based—using a competency-based selection process; (3) training includes Merdeka Curriculum workshops and capacity-building in curriculum development; (4) monitoring and evaluation are carried out regularly, both internally and externally, to assess performance and improve educational quality.